Perencanaan Pengelolaan Keuangan Desa (Studi Kasus Pada Desa Tembokrejo Kecamatan Gumukmas Kabupaten Jember) - Putri Izatul Azwa Amalia; Endro Sugiartono (Jurnal Akuntansi Terapan dan Bisnis, 2021)
This study aims to explain the financial management planning of Tembokrejo Village, as well as analyze its suitability then provide an overview of the flowchart of village financial management planning according to Permendagri Number 20 of 2018. This research is a type of qualitative research with a case study approach using primary data and data. secondary data collection procedures, namely observation, interviews, and documentation. And the data analysis technique is a comparative analysis which tests the validity of the data using the triangulation technique. Then the activities in data analysis are data reduction, data presentation, and drawing conclusions and verification. The results of this study indicate that the financial management plan of Tembokrejo Village is in accordance with the village financial management plan according to Permendagri Number 20 of 2018, due to the presence of village assistants who help in the process of preparing village financial management planning. Therefore, a flowchart was designed, which could be used as a guide to assist village officials in the process of preparing village financial management plans independently. Keywords: Village Financial Management Planning